A Novel Universal Endovascular Robot for Peripheral Arterial Stent–Assisted Angioplasty: Initial Experimental Results. (October 2020) - Lu, Qingsheng; Shen, Yu; Xia, Shibo; Chen, Bing; Wang, Kundong
Background: The bottleneck of the development of endovascular interventional robot is that it cannot fully adapt to commercialized endovascular devices, such as guidewires, catheters, and stents, and cannot complete the entire procedure of endovascular treatment, for instance, stent implantation. The purpose of this study is to evaluate whether the novel universal endovascular interventional robot can adapt to different commercialized endovascular devices and accomplish the entire procedure of endovascular treatment of peripheral vascular disease. Methods and Material: The novel universal endovascular interventional robot consists of 2 components: a master surgeon console and a robotic platform with 4 manipulators. An adult pig was served as the experimental animal. Bilateral iliac artery stent implantation was performed on the pig by the endovascular interventional robot using commercialized guidewires, catheters, and stent delivery systems. Results: The novel universal endovascular interventional robot can adapt to commercialized endovascular devices, and most interventional procedures, such as insertion, withdrawal, and rotating, can be done through remote control. By coordinating multiple manipulators, complex actions such as superselection, crossing action, or implantation of self-expanding bare stent can be realized. The entire procedure took about 50 minutes, and the total exposure time of the surgeon was less than 1 minute. Postoperative angiography showed that the position of the stent grafts was accurate. The procedure was stable without any stent or surgical-related complications. Conclusion: The novel universal endovascular interventional robot can realize peripheral arterial stent-assisted angioplasty with commercialized devices. Through the design improvement, the problem related to stent implantation is solved, and the remote operation is realized throughout the endovascular procedure.